Effects of jigsaw learning strategy integrated with computer simulations on gender differences in students’ achievement and attitude in learning chemistry - Shimelis Kebede Kekeba (Cogent Education)
This research study investigated the impact of gender and the jigsaw learning strategy integrated with computer simulations (JLSICS) on chemistry learning, emphasizing student achievement and attitudes. Chemistry is often perceived as challenging and abstract, and traditional teaching methods have not effectively addressed these difficulties. To tackle this issue, a quantitative research approach was utilized, employing a quasi-experimental design with pre- and post-tests across non-equivalent comparison groups. The study involved three intact classes: one using conventional methods (CM) and two experimental groups implementing JLSICS and the jigsaw learning strategy (JLS) independently. The sample consisted of 144 participants aged over 15. Data were collected using the Chemistry Attitude Likert Scale Test (CALST) and the Chemistry Achievement Test (CAT). The CAT’s internal consistency was assessed with the Kuder-Richardson formula 20, yielding a reliability coefficient of 0.78, while the CALST had a reliability coefficient of 0.928 based on Cronbach’s alpha. Data analysis was conducted using two-way ANOVA. The results showed that gender did not significantly influence achievement or attitudes regarding acid and base concepts. Additionally, JLSICS was found to be more effective than JLS alone and CM in improving academic success and fostering positive attitudes, regardless of gender. It is recommended that secondary school chemistry teachers adopt JLSICS to enhance student outcomes.